Análise de competências docentes na educação a distância via internet: percepção de alunos de administração - Porto, Josiane Brietzke (2013)
In the last decade we are experiencing a growth of higher education in the country. This is the result of government policies and actions to encourage economic growth in Brazil, initiatives related to higher courses of shorter duration called technological and supply in distance mode. With this, distance education has shown results in recent years in increasing their role as teaching in higher education in the country. However, this growth also comes from a maturing in general of this type of education, providing the existence of loopholes that offer opportunities for further research, discussions and reflections on various aspects of higher distance education. This includes pedagogical aspects, regulatory, management programs and courses, roles and responsibilities of individuals and institutions involved, information and communication technologies and teacher training. This work contributes to the identification of key competencies required for teaching practice in higher education distance, from the learning experience of students. The domains and competencies present in the survey instrument are defined based on the experience of the researchers, the review of literature on the subject and validation specialists. This instrument was applied in the form of survey research with students in the distance Administration graduation course. From the perception of these students, was obtained an analysis of key competencies relevant to teaching practice in EAD, as well as a mapping and analysis of the major powers present in the learning experience of these students. Regarding the importance, twenty-seven competencies were considered important by respondents in this context and form grouped into four factors, namely: Cognitive, Technological, Pedagogical and Sociocultural. As regards the assessment of presence, thirty-one competencies were considered present in the learning experience of these students and were also grouped into four distinct domains: Technological-Pedagogical, Cognitive, Sociocultural and Management.